2015
DOI: 10.1007/s00439-015-1584-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of genes important in neurodevelopment disorders in adult human brain

Abstract: Several neurodevelopmental disorders (NDDs) are caused by mutations in genes expressed in fetal brain, but little is known about these same genes in adult human brain. Here, we test the hypothesis that genes associated with NDDs continue to have a role in adult human brain to explore the idea that NDD symptoms may be partially a result of their adult function rather than just their neurodevelopmental function. To demonstrate adult brain function, we performed expression analyses and ChIPseq in human neural ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 39 publications
1
16
0
1
Order By: Relevance
“…Over the years, different genes have been shown to be involved in the regulation of cell proliferation and differentiation during cortical neurogenesis and defects in their expression have been shown to be associated with different neurodevelopmental disorders (Chen et al, 2014 ; Gigek et al, 2015 ; Maussion et al, 2015 ). T-box brain 1 ( TBR1 ) is a transcription factor expressed at a high level in early born deep layer cortical neurons and was shown to be required for differentiation of cortical progenitor cells (Hevner et al, 2001 ; Bedogni et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Over the years, different genes have been shown to be involved in the regulation of cell proliferation and differentiation during cortical neurogenesis and defects in their expression have been shown to be associated with different neurodevelopmental disorders (Chen et al, 2014 ; Gigek et al, 2015 ; Maussion et al, 2015 ). T-box brain 1 ( TBR1 ) is a transcription factor expressed at a high level in early born deep layer cortical neurons and was shown to be required for differentiation of cortical progenitor cells (Hevner et al, 2001 ; Bedogni et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have recently examined, from fetal to adult stages in several brain regions, the spatial and temporal expression patterns of genes whose mutations were found in neurodevelopmental disorders. The expression profiles suggest that all these genes are continuously expressed, and like the NTNG1 gene, have various functions depending on the period of life (Maussion et al ). The expression of either neurodevelopmental disorders or psychiatric diseases may rely on one or several gene mutations including in the NTNG1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was suggested that they disappear after 3 months of age in the human brain [ 20 , 29 ]. On the contrary, it was also reported that Satb2+ cells remain as a subpopulation in the upper cortical layers of the human brain but also extending towards layer 5 (having a predisposition for the frontal lobe) [ 30 , 31 ]. In our study, expression of Satb2 was detected in L2, 3, and 5 in both perilesional samples and postmortem controls.…”
Section: Discussionmentioning
confidence: 99%